Changes and variability of the physiological air humidity deficit index at Kasprowy Wierch (1971‑2020) and the impact of atmospheric circulation - Szokalska, Roksana; Falarz, Małgorzata (Przegląd Geograficzny)
The paper examines changes and variability of the physiological air humidity deficit index (D) at thesummit of Kasprowy Wierch in the period 1971‑2020. The analysis comprised annual and long-term patterns of the average values, absolute minima and maxima, and the number and share of days with a perception of comfort and dryness. The conditional probability of the occurrence of conditions of perceptibility of air humidity for different air masses was calculated. The highest values of the D index occur at Kasprowy Wierch in winter, the lowest – in summer. The average, maximum and minimum values of the D index in the long-term distribution show a negative trend on an annual basis. Perception of humidity comfort occurs from April to October, peaking in August. Occasionally, days with index values interpreted as sultry do occur. In the long-term period covered in the study, the share of days with perception of physiological comfort of air humidity increases significantly, while days perceived as dry decreases significantly. The conditional probability of perceiving dryness in the air is the highest during the advection of arctic air over southern Poland. For comfortable air humidity it is highest when tropical air passes over southern Poland.The high parts of the Tatra Mountains are unaffected by local anthropogenic impacts. Nevertheless, significant trends in the biometeorological index are observed, linked to air humidity conditions, which are a consequence of global climate change.